Certification Corner: A MONTHLY QUIZ: ANSWERS AND REFERENCES. Issue 4 (1st April 2014) - Unknown
Abstract : Certification Corner lets Opflow readers sharpen their skills with a quick quiz of terminology, regulations, practices, and formulas pertinent to water/wastewater distribution system and treatment plant operations.